Kamala’s Guidance and Duality in Siddhartha’s Individuation: A Jungian Psychological Analysis of Hermann Hesse’s Siddhartha an Indian Tale - Bashir, Saima; Hassan, Shahzaib; Saeed, Sohail Ahmad (Pakistan Languages and Humanities Review, 2024)
Taking Carl Jung’s concept of Self as a point of departure, the article decodes Siddhartha’s process of Individuation through his multidimensional relationship with Kamala in Hermann Hesse’s Siddhartha: An Indian Tale. Kamala the courtesan, as a teacher, a partner, and a lover, plays an indispensable role in Siddhartha’s spiritual awakening. The Jungian psychological lens is used to analyze Kamala’s unique feminine character and take her as an epitome of anima, thus conveying the unconscious feminine facets of Siddhartha’s own psyche. Her personality manifests itself as a coin embodying both the opposite sides of light and shadow animas which support Siddhartha in the nurturing of his individuality and the confrontation with the reality of the materialistic world. Siddhartha’s encounter with Kamala enhances his comprehension of the complexities of human relationships and their outcomes. Illustrating the significance of animus in Kamala’s own individuation, the study explores how Kamala’s loss in the form of her death leads the protagonist towards his destination.